Pharmacognostic studies on stem of polygonum glabrum willd - Prakash D.; Wahi S.P.; Sinha P.; Chunekar K.C.; Misra S.S. (My University, 2025)
Pharmacognostic studies on the stem of Polygonum glabrum Willd. have been carried out along with fluorescence characteristics and ash values. © 1986 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.